Faktor yang Berhubungan dengan Unmet Need pada PUS di Kecamatan Rote Timur Kabupaten Rote Ndao - Alen Muskanan; Helga Ndun; Afrona Takaeb (Yayasan Literasi Sains Indonesia, 2025)
Rote Ndao is one of the districts in NTT that is included in the top 10 districts with the highest percentage of unmet need. The percentage of unmet need among pregnant women in the Rote Ndao region was 14.80% in 2021. This study aims to determine the factors associated with the incidence of unmet need for family planning in PUS in East Rote Sub-district, Rote Ndao Regency. This research is a quantitative research with case control design. The population of PUS in this study amounted to 1,635. The number of samples consisted of 54 case samples and 54 control samples. Data were obtained by interview using a questionnaire. The data analysis used was Chi-Square. The results of data analysis showed that the level of knowledge (p-value = 0.000, OR = 11.414) and history of family planning use (p-value 0.046 = OR 2.241) were factors that had an association with the incidence of unmet need for family planning, while husband support (p-value 0.206) and the role of health workers (p-value 0.515) did not have an association with the incidence of unmet need for family planning. Some respondents did not know the benefits of using contraceptives and the risks of not using contraceptives. Most of the PUS with unmet need had a poor history of using family planning because they experienced side effects such as dizziness, amenorhea, weight changes, and headaches. Improving the knowledge of couples of childbearing age about contraceptives is necessary.